2021
DOI: 10.1371/journal.ppat.1009721
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low-density granulocytes in COVID-19

Abstract: Severe COVID-19 is characterized by extensive pulmonary complications, to which host immune responses are believed to play a role. As the major arm of innate immunity, neutrophils are one of the first cells recruited to the site of infection where their excessive activation can contribute to lung pathology. Low-density granulocytes (LDGs) are circulating neutrophils, whose numbers increase in some autoimmune diseases and cancer, but are poorly characterized in acute viral infections. Using flow cytometry, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 57 publications
6
82
0
1
Order By: Relevance
“…Recently, the work of Cabrera et al. revealed that ImN of severe COVID-19 patients had significantly more LOX-1+ cells as compared to mild cases and healthy controls ( 41 ) but T cell suppressive activity could not be evaluated. However, LOX-1 is mostly acknowledged for its role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the work of Cabrera et al. revealed that ImN of severe COVID-19 patients had significantly more LOX-1+ cells as compared to mild cases and healthy controls ( 41 ) but T cell suppressive activity could not be evaluated. However, LOX-1 is mostly acknowledged for its role in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…These LDGs spontaneously produce NETs and are favorably associated to lung inflammation and overall disease severity ( 23 ). Another study demonstrated the relationship between a cluster of CD33 low CD16 + CD11b + LDGs and increased detection of myeloperoxidase (MPO)-DNA, suggesting that this population plays a direct role in NETosis in COVID-19 ( 24 ). In addition, the presence of CD33 low CD16 + CD11b + LDGs is also associated with disease severity and prognosis.…”
Section: The Biology Of Neutrophils and Nets In Covid-19mentioning
confidence: 99%
“…Frequency of LDGs increases significantly in COVID-19 patients and correlates with disease severity [ 76 78 ], supporting earlier transcriptomic data disclosing the presence of neutrophils in PBMC from COVID-19 patients [ 79 , 80 ]. LDGs have been found to suppress the proliferation of autologous T cells in ex vivo assays and may contribute to lymphopenia and impaired immune response during severe SARS-CoV-2 infection [ 77 , 78 , 80 ]. Nonetheless, LDGs from severe COVID-19 patients, especially LDGs with intermediate CD16 expression (CD16 int LDGs), have been found to be prone to form NETs and aggregate with platelets, which promote alveolar cell apoptosis and thrombogenic coagulopathy [ 81 , 82 ].…”
Section: Role Of Ldgs In Immune-mediated Inflammatory Diseasesmentioning
confidence: 99%